Evaluatıon Of Changes In Class Iı, 2 Malocclusıons Related To Fıxed Applıance Therapy - Serdar Üşümez; Faruk Ayhan Başçiftçi (Galenos Yayinevi, 2001)
Correction of deep overbite is an essential part of the treatment of Class II, 2 malocclusions. In this study pre and post treatment cephalometric measurements of 20 Class II, 2 patients between 12 to 22 years old were compared. Of these 9 were treated with extractions and 11 with no extractions. Statistical analysis of the results demonstrated statistically significant differences between the measurements of SNB, ANB, overbite, interincisal angle, upper and lower incisor position and proclination. Correction of deep overbite was mainly related to upper and lower incisor protrusion and some upper incisor intrusion. Little or no intrusion was observed in the lower incisor. Upper and lower incisor proclinations were statistically different between extraction and nonextraction groups. Being aware of mechanism of correction of Class II, 2 malocclusions the orthodontist will be able to make better treatment plans and treatment forecasts.